Assay technologies for apoptosis and autophagy - Chitra Hariharan; Yiran Tao; Ling Jiang; Xing Wen; Jiayu Liao (Elsevier, 2021)
Cell death is an active and vital process in multicellular organisms which maintains physiological homeostasis and removes abnormal cells of the body. Dysregulation of cell death might lead to many human diseases, such as cancer. Cell death can be classified into programed cell death, such as apoptosis, autophagy, necroptosis, and non-programed cell death, such as necrosis, mitotic catastrophe. Different cell death type triggered by distinct, and sometimes overlapping signaling pathways. The qualitative detection and quantitative measurement of these modalities require the use of different methods. Therefore, available protocols and new technologies for detecting cell death are critical for research and drug discoveries. Picking the best method to identify cell death pathways in different situations requires understanding of pros and cons of each assay. Here, we summarize the pathways of cell death and assays for assessing cell death and highlight the considerations for using each method, and emphasis on recently developed fluorescence techniques.